EMOTIONAL DISTRESS AND SELF-EFFICACY AMONG HEPATITIS C PATIENTS - BIBI , S; SADDIQUE , H; TASNEEM , SS (Biological and Clinical Sciences Research Journal, 2024)
Hepatitis C is a major public health concern in Pakistan, significantly affecting patients' psychological and behavioral well-being. Emotional distress and low self-efficacy among hepatitis C patients can negatively influence disease management and overall quality of life. This study aimed to evaluate emotional distress and self-efficacy levels among hepatitis C patients in a tertiary care hospital. Methods: A descriptive cross-sectional study was conducted with 117 patients diagnosed with hepatitis C. Participants were selected through convenience sampling, and data were collected using a structured questionnaire assessing demographic characteristics, emotional distress, and self-efficacy. Statistical analysis was performed using SPSS version 26, with a p-value of <0.05 considered significant. Results: The findings revealed high levels of emotional distress, with 47% of participants frequently feeling tense and 49.6% occasionally experiencing fear. Self-efficacy scores were low, as 46.2% of participants were "not at all confident" in discussing their illness with their doctor. Younger patients exhibited better self-efficacy, while female participants reported higher emotional distress. Significant gaps in patient education and communication with healthcare providers were identified. Conclusion: Emotional distress and low self-efficacy are prevalent among hepatitis C patients in Pakistan, emphasizing the need for integrated psychological support and educational interventions in routine care. Strengthening patient-provider communication and implementing scalable mental health programs can enhance treatment adherence and patient outcomes.